2015
DOI: 10.1146/annurev-vision-082114-035835
|View full text |Cite
|
Sign up to set email alerts
|

Development of Three-Dimensional Perception in Human Infants

Abstract: The play of light on the retina contains multiple sources of information about the three-dimensional (3D) structure of the world. Some of the best information is derived from differencing operations that act on the images that result from the two eyes' laterally displaced vantage points. Other information is available in systematic retinal patterns of local texture and motion cues. This article describes what is currently known about the development of sensitivity to these binocular and monocular cues for dept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 149 publications
0
13
0
Order By: Relevance
“…The most relevant prior data for comparison to the present results is the substantial number of studies of stereo-acuity development in infants and children (for review, see Norcia and Gerhard, 2015). Stereo-acuity development is relevant here because it is controlled by mechanisms that rely on the presence of relative disparity in the display (Westheimer, 1979;McKee et al, 1990;Andrews et al, 2001). The most comparable previous study in human (Birch and Petrig, 1996) measured infant sensitivity to horizontal disparities using DRDS portraying stripes of alternating crossed and uncrossed disparity.…”
Section: Relationship To Previous Studies Of the Development Of Sterementioning
confidence: 99%
See 1 more Smart Citation
“…The most relevant prior data for comparison to the present results is the substantial number of studies of stereo-acuity development in infants and children (for review, see Norcia and Gerhard, 2015). Stereo-acuity development is relevant here because it is controlled by mechanisms that rely on the presence of relative disparity in the display (Westheimer, 1979;McKee et al, 1990;Andrews et al, 2001). The most comparable previous study in human (Birch and Petrig, 1996) measured infant sensitivity to horizontal disparities using DRDS portraying stripes of alternating crossed and uncrossed disparity.…”
Section: Relationship To Previous Studies Of the Development Of Sterementioning
confidence: 99%
“…Second, cells in V1 are primarily sensitive to absolute disparity: for example, the image disparity defined relative to the fixation plane, but not relative disparity, the difference in disparity between two or more features (Cumming and Parker, 1999;Thomas et al, 2002). The perceptual system, by contrast, is quite insensitive to absolute disparity (Westheimer, 1979;Erkelens and Collewijn, 1985;Cottereau et al, 2012a), and fine depth discrimination relies on a computation of relative disparity (Westheimer, 1979;McKee et al, 1990;Andrews et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Binocular cues to MID include interocular velocity differences (IOVD) and changing disparity (CD; Allen, Haun, Hanley, Green, & Rokers, 2015; Beverley & Regan, 1973; Brooks, 2002; Cumming & Parker, 1994; Czuba, Rokers, Huk, & Cormack, 2012; Joo, Czuba, Cormack, & Huk, 2016; Lages & Heron, 2010; Nefs, O'Hare, & Harris, 2010; Norcia & Gerhard, 2015). Previous work revealed considerable variability in binocular MID cue sensitivity across the visual field of individual observers (Barendregt, Dumoulin, & Rokers, 2014; Hong & Regan, 1989; Richards & Regan, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…Prior work in the developing human visual system using VEPs has shown that while responsiveness to absolute disparity is robust by 4–6 months of age 34 , relative disparity processing mechanisms are strikingly immature at this age 35 . Moreover, both human and non-human primate motion processing mechanisms are immature during infancy and depend on the presence of normal eye alignment during early development, implicating specifically binocular motion processing mechanisms 36 40 .…”
Section: Introductionmentioning
confidence: 89%